Phosphoric acid activated carbon as borderline and soft metal ions scavenger - Rahman, Md. Mokhlesur; Shamsudin, Siti Hadijah; Miskon, Mohd Fuad; Yunus, Kamaruzzaman; Mohd Yusof, Alias (Taylor & Francis, 2015)
Three activated carbons have been prepared, two from oil-palm shell and one from coconut shell, by the phosphoric acid activation process. Adsorption isotherms of copper(II) were determined to evaluate and compare the performance of experimental carbons. The obtained data are fitted very well to Langmuir and Freundlich adsorption models. All prepared activated carbons show 4–7-fold high adsorption capacity (qmax 19.5–23/18.6– 21 mg g−1) than that of the commercial ones (qmax 5.6/2.9 mg g−1) under the conducted experimental conditions. The mechanism of adsorption was evaluated from the competitive adsorption of copper(II) and calcium(II) in a binary solution depending on their behaviour as Lewis acid and assessed as inner-sphere complexation. The competitive adsorption of copper(II) with other borderline and soft metal ions was evaluated by the best scavenger using a solution of ternary solute of copper(II), nickel(II) and lead(II). The adsorption selectivity order is determined as follows: Pb > Cu≫Ni.